STUDY OF MANAGEMENT OF SUBTROCHANTERIC FRACTURE FEMUR BY PROXIMALFEMORAL NAILING - DR.G.KISHORE ROY,; DR.YEDLAPALLI SUBRAMANYAM, (International Journal of Pharma and Bio Sciences, 2014)
Upper femoral fractures present a peculiar problem of securing effective neutralization of deforming forces.Various upper femoral devices like dynamic condylar screw, dynamic hip screw with barrel plate, gamma nail, proximal femoral nail etc are being used by various centres and each centre claims reasonably satisfactory results with each type of device. The present study was conducted to assess the utility and effectiveness of Proximal Femoral Nail evolved by AO-ASIF in 1997, for various types of upper femoral fractures.This is a prospective study of 31 patients admitted to orthopaedic units of ASRAM Medical College Hospital between May 2007 and April2010. The most common mechanism of injury was a simple fall in females and high velocity injuries in males.This study was done to evaluate the management of subtrochanteric fracture of femur byproximalfemoral nailing.In our series of 31 cases of subtrochanteric fractures treated with Proximal Femoral Nail, 24 patients hadexcellent to good outcome at their final follow up. Fair outcome was seen in 4 patients and poor result was seen in 3 patients probably due to inappropriate reduction intraoperatively and associated degenerative joint disease of the knee.From this sample study, we conclude that Proximal Femoral Nail is a good implant for the treatment of Subtrochanteric fractures of femur provided optimal reduction of the fracture and good positioning of the implant is achieved.